Rancang Bangun Sistem Informasi Manajemen Laboratorium Komputer Menggunakan Framework CodeIgniter: indonesia - Nurmadewi, Dita (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The management of computer laboratory usage schedules at Universitas Bakrie is currently done manually, leading to difficulties in coordination and resource allocation. This issue results in inefficiencies in laboratory use and suboptimal scheduling. To address these problems, this study developed a web-based Computer Laboratory Management Information System using the CodeIgniter framework and MySQL database. The application is designed to facilitate the management of scheduling data, laboratory inventory, and the dissemination of current information to users. The system development was carried out using the waterfall method, which includes the stages of requirements analysis, system design, implementation, testing, deployment, and maintenance. The implementation results show increased efficiency and effectiveness in managing computer laboratories, with easier access to information, more orderly scheduling management, and transparency in the use of laboratory inventory. The system is built using the PHP programming language, the CodeIgniter framework, and the MySQL database to ensure optimal performance and an organized structure. The application of this method effectively addresses the manual management issues, streamlining operations, and enhancing overall productivity in laboratory management.